The state intervenes in setting prices under competition laws - Latif, Adnan Baqi; Aziz, Befrin AbdulMutalib (Journal of Legal and Political Studies, 2023)
One of the pillars of free and fair competition is freedom of prices, as there is no competition in the market without liberating prices from all possible restrictions. However, the state can, in some exceptional cases, intervene and impose restrictions on the principle of price freedom. As this exceptional intervention is a means in the hands of the state to control the market from the arbitrary practices that exist in it in order to preserve the general economic order and achieve the public interest in addition to ensuring social stability and improving the lives of consumers in order to avoid and refute the factors that impede the normal movement in the market. Therefore, despite the enshrining of the principle of freedom of prices in legislation for the protection of competition and the prevention of monopoly, most of these laws regulate special provisions and rules that allow the state to intervene in determining the prices of some necessary goods and services in exceptional circumstances, however, the Iraqi Competition and Prevention of Monopoly Law No. (14) for the year 2010 and the Competition Law and the prevention of monopoly in the Kurdistan Region -Iraq No. (3) for the year 2013 suffer from a clear lack of legal provisions regulating this exceptional interference, therefore, this study came with the aim of establishing the legal rules that regulate the intervention of the state in determining prices in a manner that does not contradict the policy of free economy that governments tend to achieve economic development and does not contradict with the philosophy of competition law that is based on leaving prices to market mechanisms, and providing effective solutions to Iraqi and Kurdistan legislators to address deficiencies in competition law and prevent monopoly in this regard.
Keywords: free and fair competition; freedom of prices; market; arbitrary practices; Kurdistan legislators